Inverse Prime?

Calculus Level 2

f ( x ) = ln ( x ) e x \large f(x)=\ln(x)e^x

Given that f 1 ( x ) f^{-1}(x) is the inverse of the function above, find d d x ( f 1 ( x ) ) \cfrac{d}{dx}\bigg(f^{-1}(x)\bigg) without working out f 1 ( x ) f^{-1}(x)

1 e f 1 ( x ) [ 1 f 1 ( x ) + ln ( f 1 ( x ) ) ] \cfrac{1}{e^{f^{-1}(x)}\left[\frac{1}{f^{-1}(x)}+\ln(f^{-1}(x))\right]} Not enough information f 1 ( x ) [ e f 1 ( x ) ln ( f 1 ( x ) ) ] f^{-1}(x)\left[ e^{f^{-1}(x)} \ln(f^{-1}(x)) \right] + 1 \infty + 1 ln ( x ) f 1 ( x ) e f 1 ( x ) \ln(x)f^{-1}(x)-e^{f^{-1}(x)} x ! × ln ( f 1 ( e x ) ) ) x! \times \ln(f^{-1}(e^x)))

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Karan Chatrath
Jul 13, 2020

Let:

z = f 1 ( x ) z = f^{-1}(x) f ( z ) = x \implies f(z) =x e z ln z = x \implies \mathrm{e}^{z}\ln{z} =x

Differentiating both sides with respect to x x :

e z ( 1 z + ln z ) d z d x = 1 \mathrm{e}^{z}\left(\frac{1}{z} + \ln{z}\right)\frac{dz}{dx} = 1 d z d x = 1 e z ( 1 z + ln z ) \implies \frac{dz}{dx} = \frac{1}{\mathrm{e}^{z}\left(\frac{1}{z} + \ln{z}\right)}

Recall that

z = f 1 ( x ) z = f^{-1}(x) d d x ( f 1 ( x ) ) = 1 e f 1 ( x ) ( 1 f 1 ( x ) + ln ( f 1 ( x ) ) ) \implies \boxed{\frac{d}{dx} \left( f^{-1}(x)\right) = \frac{1}{\mathrm{e}^{f^{-1}(x)}\left(\frac{1}{f^{-1}(x)} + \ln\left(f^{-1}(x)\right)\right)}}

Chew-Seong Cheong
Jul 14, 2020

Let y = f ( x ) y=f(x) . Then we have y = e x ln x y = e^x \ln x . d y d x = e x ln x + e x x \implies \dfrac {dy}{dx} = e^x \ln x + \dfrac {e^x}x and d x d y = 1 e x ln x + e x x \dfrac {dx}{dy} = \dfrac 1{e^x \ln x + \frac {e^x}x} . Replace y y with x) and \(x with f 1 ( x ) f^{-1}(x) . we have:

d f 1 ( x ) d x = 1 e f 1 ( x ) ( ln ( f 1 ( x ) ) + 1 f 1 ( x ) ) \frac {d f^{-1}(x)}{dx} = \boxed{\frac 1{e^{f^{-1}(x)}\left(\ln (f^{-1}(x)) + \frac 1{f^{-1}(x)}\right)}}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...